PAME Work Plan 2017-2019 - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment, 2017)
PAME's Work Plan 2017-2019 was developed i.a., according to PAME's mandate and direction provided in Ministerial declarations. PAME focuses on the marine agenda of the Arctic Council and provides a unique forum for collaboration on a wide range of activities directed towards the protection and sustainable use of the Arctic marine environment.